Answer:
The rule (n×2+1) gives the sequence of odd numbers {.... , -5, -3, -1, 1, 3, 5, ....}.
Explanation:
We have the expression 'n×2+1'.
It is required to find a pattern obtained by the expression.
Substituting values of 'n' gives,
For n = -3, we get (n×2+1) = (-3×2+1) = -6+1 = -5
For n = -2, we get (n×2+1) = (-2×2+1) = -4+1 = -3
For n = -1, we get (n×2+1) = (-1×2+1) = -2+1 = -1
For n = 0, we get (n×2+1) = (0×2+1) = 1
For n = 1, we get (n×2+1) = (1×2+1) = 2+1 = 3
For n = 2, we get (n×2+1) = (2×2+1) = 4+1 = 5
So, we see that, substituting the value of n, the result comes out to be an odd number.
Hence, the rule (n×2+1) gives the sequence of odd numbers {.... , -5, -3, -1, 1, 3, 5, ....}.